Ab Initio Calculation of UV-Vis Absorption Spectra of a Single Chlorophyll a Molecule: Comparison Study between RHF/CIS, TDDFT, and Semi-Empirical Methods - Veinardi Suendo; Sparisoma Viridi (Institute for Research and Community Services (LPPM) ITB, 2012)
Chlorophyll a is the most abundant pigment on Earth responsible for trapping light energy to perform photosynthesis in green plants. This molecule has been studied for many years from different points of interest with both experimental and theoretical methods. In this study, the Restricted Hartree-Fock/Configuration Interaction Single (RHF/CIS), Time-Dependent Density Functional Theory (TDDFT), and several semi-empirical methods (CNDO/S and ZINDO) calculations were carried out to reconstruct the UV-Vis absorption spectra of chlorophyll a. To some extent, the calculation results based on the single-molecule approach succeeded to reconstruct the absorption spectra, but they required to be rescaled to fit the experimental results. In general, the semiempirical methods provide a better energy scaling factor. However, they lack vertical transition fine features with respect to the spectrum obtained experimentally. In this case, the ab initio calculations provided more complete features, especially the TDDFT with high-level basis sets, which also has a good accuracy with regards to the transition energies. The contribution of the ground state and excited state orbitals in the main vertical transitions is discussed based on the delocalized nature of the wave functions and the presence of solvents using the polarizable continuum model (PCM).